The effects of outdoor sensory garden on activity participation in children with Autism Spectrum Disorders - SILPA IMMANUEL VOOLA,; MERLYN SHEEBA,; PRINCE K, (International Journal of Pharma and Bio Sciences, 2018)
Autism spectrum disorders (ASD) are life-long neuro developmental disorders characterized by impairments in three domains of functioning: social behavior, communication abilities, and restricted, repetitive or stereotyped patterns of behaviour which aretypically noticed in the first 3 years of life. Researchers have revealed that going back to nature is gaining popularity and significance Hence,this study was done to find out the effects of sensory garden on activity participation among ASD children. This was a Quasi experimental pre and post test design study. Sixteen children aged 4-12 years were recruited by screening with Short Sensory Profile and Childhood Autism Rating Scale.The data was collected at baseline and post intervention for activity participation using the global score of Child and Adolescent Scale of Participation (CASP).The subjects were divided equally into experimental and control group through convenience sampling. The experimental group was provided with sensory based activities targeting all the seven senses through sensory garden along with Sensory Integration (SI) intervention and the control group was provided with only SI intervention for 2 months. Non parametric tests Wilcoxon Signed Rank test and Mann Whitney U test at 5 % significance level were used to find within the group and between the group mean respectively .The findings of this study reveals that, sensory garden (outdoor sensory based activities) is an effective therapeutic procedure in children with ASD to enhance activity participation.